2016
DOI: 10.1007/s41101-016-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of Locally Used Plant Coagulants for Household Water Treatment

Abstract: Conventional chemical water treatment systems which involve a series of steps are not feasible in rural areas, where a dispersed population is found. Moreover, it is extremely costly for investment in developing countries. Hence, improving drinking water quality at a household level is believed to be effective in fighting waterborne diseases. For this purpose, we investigated the performance of indigenous plant species locally used for turbid water treatment in Ethiopia. Batch coagulation and microbial reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The plant extracts showed microbial removal efficiency up to 80% on different turbidity levels of well water in Malawi. A similar study conducted by Megersa et al reported efficient reduction (99.9%) of faecal coliforms from turbid river.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…The plant extracts showed microbial removal efficiency up to 80% on different turbidity levels of well water in Malawi. A similar study conducted by Megersa et al reported efficient reduction (99.9%) of faecal coliforms from turbid river.…”
Section: Introductionsupporting
confidence: 60%
“…For instance, seeds of Vigna unguiculata and Parkinsonia aculeata are used by local people of Tanzania, whereas indigenous people of Venezuela use seeds of Cactus latifaria and Prosopis juliflora for turbid water treatment . It has been reported in various studies that some plant species may have the ability to kill microorganisms beyond their coagulation ability . For instance, Pritchard et al tested the coagulation and disinfection ability of Jatropha curcas on shallow well water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sasikala & Muthuraman [13] mentioned in their study that Moringa oleifera coagulation efficiency is particularly good at pH acidic which is at less than 6 and also pH that is greater than 11 dues to the influence of positive charges on the amino acids that builds up the protein molecule. Both coagulants trend of reduction was seen to increased and decreased constantly due to the hydrolysis where the hydrogen ions are balancing out the hydroxide ions for both of the coagulants [9]. But nevertheless, the most important finding is aluminum sulphate usage was seen to lower the pH of the groundwater sample to acidic, while for the usage of Moringa oleifera as caogulant is that they do not cause water to turn acidic as compared to when aluminium sulphate was used.…”
Section: Phmentioning
confidence: 97%